The curse of Ham : race and slavery in early Judaism, Christianity, and Islam - Goldenberg, David (Princeton, N.J. : Princeton University Press, 2003)
"In this book, David Goldenberg seeks to discover how dark-skinned peoples, especially black Africans, were portrayed in the Bible and by those who interpreted the Bible - Jews, Christians, and Muslims. Unprecedented in rigor and breadth, his investigation covers a 1,500-year period, from ancient Israel (around 800 B.C.E.) to the eighth century C.E., after the birth of Islam. By tracing the development of anti-Black sentiment during this time, Goldenberg uncovers views about race, color, and slavery that took shape over the centuries - most centrally, the belief that the biblical Ham and his descendants, the black Africans, had been cursed by God with eternal slavery."--BOOK JACKET.
Pt. 1. Images of Blacks -- 1. Biblical Israel: The Land of Kush -- 2. Biblical Israel: The People of Kush -- 3. Postbiblical Israel: Black Africa -- 4. Postbiblical Israel: Black Africans -- Pt. 2. The Color of Skin -- 5. The Color of Women -- 6. The Color of Health -- 7. The Colors of Mankind -- 8. The Colored Meaning of Kushite in Postbiblical Literature -- Pt. 3. History -- 9. Evidence for Black Slaves in Israel -- Pt. 4. At the Crossroads of History and Exegesis -- 10. Was Ham Black? -- 11. "Ham Sinned and Canaan was Cursed?!" -- 12. The Curse of Ham -- 13. The Curse of Cain -- 14. The New World Order: Humanity by Physiognomy -- Conclusion: Jewish Views of Black Africans and the Development of Anti-Black Sentiment in Western Thought -- App. I. When is a Kushite not a Kushite? Cases of Mistaken Identity -- App. II. Kush/Ethiopia and India.
Includes bibliographical references (p. [213]-378) and indexes.
Keywords: Ham -- (Biblical figure); Bible. -- Criticism, interpretation, etc. -- History -- To 1500.; Blacks in the Bible; Blacks -- Public opinion -- History -- To 1500.; Jews -- Attitudes -- History -- To 1500.; Christians -- Attitudes -- History -- To 1500.; Muslims -- Attitudes -- History -- To 1500.; Slavery -- Justification -- History; Black race -- Color